RETRACTED: Experimental determination of the parameters of the adaptive support of the power unit of the machine-tractor unit - Khaliullin Farit; Zimina Larisa; Egorov Sergey; Khaliullin Airat; Pikmullin Gennady; Molochnikov Denis (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001